2020
DOI: 10.3892/etm.2020.9193
|View full text |Cite
|
Sign up to set email alerts
|

circKMT2D contributes to H<sub>2</sub>O<sub>2</sub>‑attenuated osteosarcoma progression via the miR‑210/autophagy pathway

Abstract: Circular RNAs (circRNAs) have been demonstrated to be involved in osteosarcoma (OS) development; however, the underlying mechanism of circKMT2D in OS progression remains unclear. The present study aimed to elucidate how circKMT2D could affect hydrogen peroxide (H 2 O 2)-induced OS progression. H 2 O 2 (100 µmol/l) was used to treat MG63 and U2OS cells. The cell viability, invasive ability, apoptosis and circKMT2D expression were detected using Cell Counting Kit-8 assay, Transwell assay, flow cytometry and reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…2 ). Zhang et al [ 25 ] screened some key genes involved in the development of osteosarcoma, including miRNAs, which may be related to the metastasis of osteosarcoma. They found miR-210 overexpression elevated Beclin-1 expression and decreased p62 expression in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). Zhang et al [ 25 ] screened some key genes involved in the development of osteosarcoma, including miRNAs, which may be related to the metastasis of osteosarcoma. They found miR-210 overexpression elevated Beclin-1 expression and decreased p62 expression in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The miR-432-5p/HDAC4 axis has been shown to mediate the oncogenic roles of circCRIM1. Zhang et al (2020b) found that H 2 O 2 refrained the progression of osteosarcoma, while upregulating the circKMT2D in osteosarcoma. Following explorations demonstrated that silencing circKMT2D markedly impaired the viability and metastasis of osteosarcoma, while activating the autophagy process and strengthening the anti-cancer effect of H 2 O 2 .…”
Section: Main Textmentioning
confidence: 94%
“…circRNAs have three main functions: i) Serving as microRNA (miR/miRNA) sponges to sequester and inhibit miRNA activity; ii) acting as regulators that interact with proteins; iii) serving as templates for protein synthesis (8). circRNAs play an important role in the development and progression of human tumors, according to accumulating evidence (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%